The impact of work–life balance and flexible work arrangements on non‐financial organisational performance. - William, Asamoah‐Appiah; Singh, Kesari (International Social Science Journal, 2024)
The study's goal was to determine the effect of work–life balance (WLB) and flexible work arrangements (FWAs) on non‐financial organisational performance. The study was motivated by a lack of empirical research on the impact of WLB and FWA on organisational non‐financial performance in developing countries. The evaluation of organisational performance is skewed towards financial indicators at the expense of non‐financial metrics. The study's population consisted of management and non‐management employees from seven multinational and national manufacturing and service firms. Based on a population of 1068 people, the sample size was 678. The return rate was 86.72%. The respondents were chosen using a simple random sampling technique with the aid of a table of random numbers. The research design was a survey, with a validated structured questionnaire used. The data was quantitative, and it was analysed using SPSS (IBM, vr. 26) and SEM‐PLS (3.0). The main findings were that there was a statistically significant relationship among WLB, FWAs and non‐financial organisational performance. It was suggested that management include non‐financial performance indicators in performance evaluations and implement WLB and FWA policies to reduce paid work inferences with personal life.